Formation of Dense Pore Structure by Te Addition in Bi0.5Sb1.5Te3: An Approach to Minimize Lattice Thermal Conductivity. (7th November 2013) - Hasan, Syed Waqar; Mun, Hyeona; Kim, Sang Il; Cho, Jung Young; Roh, Jong Wook; Yang, Sangsun; Choi, Soon-Mok; Lee, Kyu Hyoung; Kim, Sung Wng
Abstract : We herein report the electronic and thermal transport properties of p-type Bi0.5 Sb1.5 Te3 polycrystalline bulks with dense pore structure. Dense pore structure was fabricated by vaporization of residual Te during the pressureless annealing of spark plasma sintered bulks of Te coated Bi0.5 Sb1.5 Te3 powders. The lattice thermal conductivity was effectively reduced to the value of 0.35 W m −1 K −1 at 300 K mainly due to the phonon scattering by pores, while the power factor was not significantly affected. An enhanced Z T of 1.24 at 300 K was obtained in spark plasma sintered and annealed bulks of 3 wt.% Te coated Bi0.5 Sb1.5 Te3 by these synergetic effects.